Internet Shutdown, Exam Fear and Role of Libraries: A Survey among PG students of Assam University Silchar (LIS TODAY, 2021)
The present survey was conducted to find out that how library comes handy in crucial time  like shutting of internet by the Government during exam time. Library emerged as a savior for the  students. During an internet shutdown, students are barely accessible to the information. Thus this  survey reveals that PG students of Assam University prefer to find the resources they find through the  internet more easier than the resources available in their library. The shutting down of internet  during exam time does leads the students to the psychological phase and thus this phenomenon  resulted in fear of failure in exam. The researcher evaluated every perspective of the present study  that directly or indirectly related to the PG students of Assam University Silchar about their views on  how their library and library professional helps them in internet shutdown during exam time.  However, every research has a future scope.
Keywords: Internet Shutdown; Exam Fear; Role of Library; University Library; Assam University Silchar